Subacute inhalation exposure to ozone induces systemic inflammation but not insulin resistance in a diabetic mouse model. (20th March 2016) - Ying, Zhekang; Allen, Katryn; Zhong, Jixin; Chen, Minjie; Williams, Keisha M.; Wagner, James G.; Lewandowski, Ryan; Sun, Qinghua; Rajagopalan, Sanjay; Harkema, Jack R.
Abstract: Epidemiological studies suggest that diabetics may be more susceptible to the adverse health effects from exposure to high ambient concentrations of ozone, the primary oxidant gas in photochemical smog. While increased morbidity and mortality from ozone inhalation has been linked to disruption of normal cardiovascular and airway functions, potential effects on glucose and insulin homeostasis are not understood. We tested the hypothesis that ozone exposure would worsen metabolic homeostasis in KKAy mice, a genetic diabetic animal model. Male KKAy mice were exposed to 0.5 ppm ozone for 13 consecutive weekdays, and then assessed for airway, adipose and systemic inflammation, glucose homeostasis, and insulin signaling. Ozone exposure increased plasma TNFα, as well as expression of VCAM-1, iNOS and IL-6 in both pulmonary and adipose tissues. Pro-inflammatory CD11b + Gr-1 lo 7/4 hi macrophages were increased by 200% in adipose tissue, but unchanged in blood. Interestingly, glucose levels were not significantly different in the insulin tolerance test between air- and ozone-exposed mice, whereas fasting insulin levels and HOMA-IR in ozone-exposed animals were significantly reduced. These changes were accompanied by increased insulin signaling in skeletal muscle and liver, but not adipose tissues. Ozone also caused decrease in body weight and plasma leptin. Our results show that in addition to marked local and systemic inflammation, ozone increases insulin sensitivity that may be related to weight loss/leptin sensitization-dependent mechanisms in KKAy mice, warranting further study on the role of hyperglycemia in mediating cardiometabolic effects of ozone inhalation.